Pharmacotherapies for cannabis dependence - Nielsen, Suzanne (Cochrane Database Syst Rev, 2019)
BACKGROUND: Globally, cannabis use is prevalent and widespread. There are currently no pharmacotherapies approved for treatment of cannabis use disorders. This is an update of a Cochrane Review first published in the Cochrane Library in Issue 12, 2014. OBJECTIVES: To assess the effectiveness and safety of pharmacotherapies as compared with each other, placebo or no pharmacotherapy (supportive care) for reducing symptoms of cannabis withdrawal and promoting cessation or reduction of cannabis use. SEARCH METHODS: We updated our searches of the following databases to March 2018: the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, PsycINFO and Web of Science. SELECTION CRITERIA: Randomised controlled trials (RCTs) and quasi‐RCTs involving the use of medications to treat cannabis withdrawal or to promote cessation or reduction of cannabis use, or both, in comparison with other medications, placebo or no medication (supportive care) in people diagnosed as cannabis dependent or who were likely to be dependent. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. MAIN RESULTS: We included 21 RCTs involving 1755 participants: 18 studies recruited adults (mean age 22 to 41 years); three studies targeted young people (mean age 20 years). Most (75%) participants were male. The studies were at low risk of performance, detection and selective outcome reporting bias. One study was at risk of selection bias, and three studies were at risk of attrition bias. All studies involved comparison of active medication and placebo. The medications were diverse, as were the outcomes reported, which limited the extent of analysis. Abstinence at end of treatment was no more likely with Δ(9)‐tetrahydrocannabinol (THC) preparations than with placebo (risk ratio (RR) 0.98, 95% confidence interval (CI) 0.64 to 1.52; 305 participants; 3 studies; moderate‐quality evidence). For selective serotonin reuptake inhibitor (SSRI) antidepressants, mixed action antidepressants, anticonvulsants and mood stabilisers, buspirone and N‐acetylcysteine, there was no difference in the likelihood of abstinence at end of treatment compared to placebo (low‐ to very low‐quality evidence). There was qualitative evidence of reduced intensity of withdrawal symptoms with THC preparations compared to placebo. For other pharmacotherapies, this outcome was either not examined, or no significant differences was reported. Adverse effects were no more likely with THC preparations (RR 1.02, 95% CI 0.89 to 1.17; 318 participants; 3 studies) or N‐acetylcysteine (RR 0.94, 95% CI 0.71 to 1.23; 418 participants; 2 studies) compared to placebo (moderate‐quality evidence). For SSRI antidepressants, mixed action antidepressants, buspirone and N‐acetylcysteine, there was no difference in adverse effects compared to placebo (low‐ to very low‐quality evidence). There was no difference in the likelihood of withdrawal from treatment due to adverse effects with THC preparations, SSRIs antidepressants, mixed action antidepressants, anticonvulsants and mood stabilisers, buspirone and N‐acetylcysteine compared to placebo (low‐ to very low‐quality evidence). There was no difference in the likelihood of treatment completion with THC preparations, SSRI antidepressants, mixed action antidepressants and buspirone compared to placebo (low‐ to very low‐quality evidence) or with N‐acetylcysteine compared to placebo (RR 1.06, 95% CI 0.93 to 1.21; 418 participants; 2 studies; moderate‐quality evidence). Anticonvulsants and mood stabilisers appeared to reduce the likelihood of treatment completion (RR 0.66, 95% CI 0.47 to 0.92; 141 participants; 3 studies; low‐quality evidence). Available evidence on gabapentin (anticonvulsant), oxytocin (neuropeptide) and atomoxetine was insufficient for estimates of effectiveness. AUTHORS' CONCLUSIONS: There is incomplete evidence for all of the pharmacotherapies investigated, and for many outcomes the quality of the evidence was low or very low. Findings indicate that SSRI antidepressants, mixed action antidepressants, bupropion, buspirone and atomoxetine are probably of little value in the treatment of cannabis dependence. Given the limited evidence of efficacy, THC preparations should be considered still experimental, with some positive effects on withdrawal symptoms and craving. The evidence base for the anticonvulsant gabapentin, oxytocin, and N‐acetylcysteine is weak, but these medications are also worth further investigation.